The Implementation of the Strategy of Marketing Management through a SWOT Analysis with the Matrix of IFE, EFE and IE - Ara Fathia Az Zahra; Wahyudin Wahyudin; Billy Nugraha (Jurnal Serambi Engineering, 2021)
The level of competition is usually influenced by a variety of factors such as: promotions, services, security and others. This study aims to analyze the implementation of the strategy of marketing management SME snacks. Although it already has a fairly large market share, but the bare possibility of the presence of competitors engaged in the same field. Then the right strategy is to use the analysis of strength, weaknesses, opportunities and threat (SWOT). In addition, with the approach of matrix internal factor evaluation (IFE), matrix external factor evaluation (EFE) and the matrix internal external (IE). Renewal in the research is the use of the IFE, EFE and IE matrix. This is so that the results of the assessment can determine the position and strength of the business. Then the results of the study show that SME snacks have 8 strength, 7 weaknesses, 6 opportunities and a 5 threat. In addition, the results of the IFE matrix is weighted by 2.74 this show is in the position of the average. While the results of the EFE matrix weighted by 3.01 it is shown to be in a strong position. While the results of the IE matrix is in quadrant II, it is within the scope of a strategy to growth and nurture (growth and build).